PENGARUH PEMBERIAN FILTRAT DAUN ALANG-ALANG (IMPERATA CYLINDRICA L.) TERHADAP PERTUMBUHAN MISELIUM JAMUR TRICHODERMA SP. YANG HIDUP PADA MEDIA TANAM JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) - KURNIA WATI, DIAN Kurnia (LenteraBio: Berkala Ilmiah Biologi, 2012)
The genus Trichoderma is cosmopolitan in soil, on decaying wood and vegetable matter. Infections in mushroom cultivation due to member of genus Trichoderma have come to be know as the ?Green Mould? dieases. Among the fungal pathogens, Trichoderma viridae are the most common dieases that can causes loss in Oyster mushroom (Pleurotus ostreatus) cultivation. If Trichoderma have been found on cultivated Oyster mushroom (Pleurotus ostreatus), the farmers  should throw it away the baglog, to prevant another baglog contaminated. This research aimed to investigate the effect of adding alang-alang (Imperata cylindrica L.) leves filtrate on the growth of Trichoderma sp. cultured on Pleurotus ostreatus media. This research use the Complete Randome Disign (CRD) with 5 treatment consentration. The concentration was:  10%,20%, 30%, 40% dan 0% (controlled). Each treatment replicated into five times. The result, which includes the width surface of mycellium colony of Trichoderma sp. and the width surface of mycellium colony of oyster mushroom (Pleurotus ostreatus), is descriptively analyzed. Based on the average width of both surface mycellium colony, it is known that there is significant different growth. The lowest width of Trichoderma sp. growth which found on the 40% concentration is 7,925 cm2. The highest width of oyster mushroom (Pleurotus ostreatus) growth which found on the 40% concentration is 2063,200 cm2.